Exploring the Phytochemicals, Antioxidant Capacity and Cytotoxicity of Abroma augustum (L.) L.f. Seed Extract, an In vitro Study (Plant Tissue Culture and Biotechnology, 2025)
The antioxidant activity of Abroma augustum extract was tested via an in vitro method using zebrafish embryos in a manner similar to that used for the cytotoxicity assay. Important phytochemicals like, alkaloids, carbohydrates, flavonoids, glycosides, phenols, polyphenols and tannins were identified from methanol extract of A. augustum seed extract. In terms of antioxidancy, the highest 1, 1-diphenyl-2-picrylhydrazyl radical (DPPH) inhibition rates were 65.30 ± 0.9% and 80.85 ± 1.0% for A. augustum seed extract and tert-butyl-1-hydroxytoluene (BHT), respectively. The concentration that inhibits 50% (IC50) value of the seed extract was 105.57 ± 1.19 and the BHT value was 88.89 ± 1.0 μg/ml. In the cytotoxicity test, at 96 hrs post fertilization (hpf), treatment with 100 μg/ml seed extract resulted in yolk sac edema, tail deformation and pericardial edema. The present study may be helpful to screen for major classes of phytochemicals and to evaluate the antioxidant and cytotoxic activities of Abroma augustum seed extract. The present findings may also be helpful for the development of anticancer and antimicrobial drugs design in the near future.Plant Tissue Cult. & Biotech. 35(1): 219-227, 2025 (June)